Effects of medium-height mountain training on the functional abilities and physical fitness of mid-distance runners - Sosnovsky, V. V.; Pastukhova, V. A.; Pornichenko, V. I.; Filippov, M. M.; Ilyin, V. M. (Journal of Physical Education and Sport, 2019)
The purpose of this study was to identify functional changes that determine the effectiveness of mountain training for athletes specializing in running medium distances, after return from mountain.Twelve elite athletes specializing in running distances of 400 and 800mparticipated in this study and were measured 2 times, with rest periods of 20 days between measurements.Our results show that mountain training leads to an increase in the physical performance and the level of physical fitnesslasting as long as 24-25 days after returning from the mountains. However, not for all athletes training is equally effective.The most significant positive changes are observed in athletes whose adaptation to the conditions of the medium-height mountainsis accompanied by moderate intensity of regulatory mechanisms and prevalence of the vagotonic type of autonomic homeostasis.Differences in reactions to hypoxia maybe also due to the individual characteristics of athletes, e.g. the genetic predisposition to a favorable response to hypoxia, the type of central and autonomic nervous system, or efficiently planned mountain training.Thus it is important to split athletes into groups according to their reaction to hypoxia while planning efficient training programs at mid altitudes.